Knowledge about HIV/AIDS among the dental students in Dhaka - Mohammed Shahed Jahan; Mushfiq Hassan Shaikh; Jahanara Begum; Tazdik G Chowdhury; Morshed Hasan (Update Dental College Journal, 2013)
Aims:This was a cross-sectional study done in the City Dental College, Malibagh, Chowdhurypara. The objective of the study was to assess the level of knowledge about HIV/AIDS among the final year dental students during the period between April to June 2012.